2012
DOI: 10.3109/15563650.2012.709936
|View full text |Cite
|
Sign up to set email alerts
|

Hazard of household cleaning products: A study undertaken by the UK National Poisons Information Service

Abstract: In the UK, advice from the NPIS is sought commonly regarding household products, but such exposures only rarely result in clinically serious features. As 65.5% of exposures were in children less than 5 years of age, parents clearly have an important role to play in ensuring that household products are stored safely at all times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
35
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 23 publications
0
35
0
1
Order By: Relevance
“…Studies from the United Kingdom have characterized the most common routes of pod exposure among children, the severity of these exposures, and clinical features seen with each route of exposure. 6,9,10 Detrimental ocular effects, including conjunctivitis, keratitis, and corneal epithelial burns, after ocular exposures to detergent pods have been welldocumented in European literature and recently in Canadian case studies. 6,11,12 In Italy, laundry detergent pods have become the most commonly ingested household product since becoming available in 2010.…”
mentioning
confidence: 99%
“…Studies from the United Kingdom have characterized the most common routes of pod exposure among children, the severity of these exposures, and clinical features seen with each route of exposure. 6,9,10 Detrimental ocular effects, including conjunctivitis, keratitis, and corneal epithelial burns, after ocular exposures to detergent pods have been welldocumented in European literature and recently in Canadian case studies. 6,11,12 In Italy, laundry detergent pods have become the most commonly ingested household product since becoming available in 2010.…”
mentioning
confidence: 99%
“…1 Laundry detergent packets were available in the European market more than 10 years earlier than in the United States, and statistics on ingestion among European children mirror those in the United States. 2,3 Results of a national poison center study from the United Kingdom indicated that exposures to laundry detergent packets were the highest proportion of exposures to household cleaning products; 96% of the exposures occurred in children less than 5 years old, and 80% occurred via ingestion. 2 Data from US and European studies 2,8 indicated that compared with exposure to nonpacket forms of laundry detergents, ingestion of packets resulted in more signs and symptoms and increased emesis, drowsiness, coughing or choking, digestive signs and symptoms, and bronchospasm.…”
Section: Introductionmentioning
confidence: 99%
“…11 Reports of substantial toxic effects after ingestion or exposure highlight the risk that laundry detergent packets pose to children. [1][2][3][4][5][6][7][8][9][10] From March 2012 to April 2013, a total of 17 230 exposures of children to laundry detergent packets were reported to the National Poison Data System. 1 The number includes ocular and dermal exposures, ingestions, and aspiration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laundry detergent pods (LDPs) are a new form of concentrated laundry detergent covered by a membrane designed to dissolve in water, made from a material such as polyvinyl alcohol [1][2][3][4][5] . Most of these capsules are colorful and perceived as toys or candies by pediatric patients, especially those under 5 years of age 2,6 .…”
mentioning
confidence: 99%